NILAI PENDIDIKAN ISLAM DALAM PERSPEKTIF ISLAMISASI DAN INTEGRASI ILMU (ISMAIL RAJI AL FARUQI, SYED MUHAMMAD NAQUIB AL ATTAS, AMIN ABDULLAH) - Ahmad Yazid Hayatul Maky; Khojir Khojir (Cross-border, 2021)
The breadth of science in various kinds of studies, both those that develop in the Islamic world or those that develop in the western world, gave birth to two different sides of thought, western scholarship with all its achievements in progress which stems from the development of Greek philosophy that leads to modern thinking models. Meanwhile, Islamic scholarship which refers to the holy book of the Qur'an and Hadith leads to the purification of thought. So that from these two scientific sides, there are several scientific principles that are contradictory and even contradictory. So far, Islamic thought is fragmentary and has no connection with contemporary issues. Therefore, efforts are needed to build an integrative-interconnective scientific epistemology. The purpose of this paper is to look at some of the thoughts of Islamization and scientific integration of Ismail Raji Al Faruqi, Syed Muhammad Naquib Al Attas and Amin. This writing method is in the form of a literature review (Library Research). Data analysis was carried out using the technique of deepening Islamic thought from Ismail Raji Al Faruqi, Syed Muhammad Naquib Al Attas and Amin Abdullah. The results of the paper describe that the Islamization and Integration of Science in Islamic Religious Education is Amin Abdullah's scientific spider web model, the integration of western science with the Ismail Raji model and the Islamization of science with the Syed Naquib Al Attas model.